Development of a multi-adaptive feeding device for automated plug seedling transplanter - Shao, Yuanyuan; Han, Xiang; Xuan, Guantao; Liu, Yi; Gao, Chong; Wang, Gongpu; Hu, Zhichao (International Journal of Agricultural and Biological Engineering, 2021)
In order to improve the adaptability of the seedling feeding devices to different plug trays for various seedlings, a multi-adaptive plug seedling feeding device for automatic field transplantation was developed. Its efficiency and adaptability have been improved using a seedling delivery device equipped with a row of end-effectors, which were provided with continuous plug seedlings by a compact seedling tray conveyor carrying out a reciprocating action. Each operation for the seedling feeding device could work automatically through a control system. Three categories of plug seedlings, cucumber, pepper and tomato seedlings, were tested. The results of the performance test for the prototype demonstrated that the best performance emerged in the cucumber seedlings in 50-cell trays with the highest success rate of 88% at the feeding frequency of 6 groups/min. The lowest success rate was 73.33% for the tomato seedlings in 105-cell trays at the feeding frequency of 12 groups/min. It can be concluded that the automated feeding device developed in this study could be used for various plug seedlings as a result of its strong adaptability. Keywords: plug seedling, automated feeding device, vegetable transplanting, control system DOI: 10.25165/j.ijabe.20211402.6003 Citation: Shao Y Y, Han X, Xuan G T, Liu Y, Gao C, Wang G P, et al. Development of a multi-adaptive feeding device for automated plug seedling transplanter. Int J Agric & Biol Eng, 2021; 14(2): 91–96.